Crystallization kinetics, morphology, and hydrolytic degradation of novel bio‐based poly(lactic acid)/crystalline silk nano‐discs nanobiocomposites. Issue 33 (6th May 2018) - Patwa, Rahul; Kumar, Amit; Katiyar, Vimal
ABSTRACT: In this work, novel biodegradable crystalline silk nano‐discs (CSNs) having a disc‐like morphology have been utilized for fabrication of poly(lactic acid) (PLA) nanocomposites by melt‐extrusion. The main focus is to investigate the effect of CSN on isothermal melt crystallization kinetics, spherulitic growth rates, morphology, and hydrolytic degradation of PLA. Spherulitic morphology and growth rates are examined over a wide range of crystallization temperatures (90–120 °C). With incorporation of CSN, the isothermal crystallization kinetics of PLA/CSN increases, however, the crystallization mechanism remains unaltered. The apparent activation energy and surface energy barrier for crystallization process decreases upon addition of CSNs. At lower isothermal crystallization temperatures ( Tc ) viz. (90–100 °C), reduced growth rates of PLA spherulites is observed. Both PLA and PLA/CSN exhibit highest crystallization rates at around ∼107 °C. The hydrolytic degradation rates calculated from molecular weight reduction shows that PLA/CSN nanocomposites' degradation rates are lower as compared to PLA in acidic, neutral, and alkaline media at pH = 2, 7, and 12, respectively, due to hydrophobic nature of CSN. Scanning electron microscopy study demonstrated the surface erosion mechanism of hydrolytic degradation of PLA and PLA/CSN nanocomposites. This work provides valuable insight for the application and reclamation of PLA/CSN bionanocomposites in moist and wet working environments. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46590. Abstract :